Acute effect of caffeine in resistance training - Moura, Dagnou Pessoa de [UNESP]; Lavor, Eduardo [UNESP]; Ribeiro da Silva, Luiz Augusto [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2017)
Caffeine is one of the substances being used by practitioners of physical activity in order to delay fatigue. The aim of this study was to investigate the influence of supplementation of 5 mg / kg caffeine on performance in resistance training. We selected seven individuals aged 24.14 +/- 2.67 years, 1.75 +/- 0.05 meters high, 20.62 +/- 5.10% body fat and BMI 24.96 +/- 1.71 kg /m2. The group performed resistance training to 70% of 1RM for chest and triceps exercises performed until exhaustion. Randomly performed without the use of caffeine training (WC), using placebo (PL) and consuming 5 mg /kg (CC) 30 minutes before activity. It was adopted 1-minute rest between sets and 2 minutes to exchange exercise. To calculating the total amount of training was: total amount = series x repetitions x weight (kg). Repetitions throughout the training session were 150.86 +/- 16.19 (SC), 150.14 +/- 26.40 (PL) and 157.14 +/- 25.40 (CC). The total amount in kilograms in the same order was 20028 +/- 2950.78 (WC) 20808 +/- 484.26 (PL) and 21402 +/- 4925.69 (CC). There was no statistical difference between the results achieved in the training sessions. It is concluded in this study that the use of caffeine does not improve performance in resistance training.
Keywords: Resistance Training; Stimulants